Effect of fermented heat-treated rice bran on performance and possible role of intestinal microbiota in laying hens - Wang, Yamei; Zheng, Weijiang; Deng, Wei; Fang, Hua; Hu, Heng; Zhu, He; Yao, Wen (Frontiers in Microbiology, 2023)
Rice bran is a high-quality and renewable livestock feed material rich in nutrients and bioactive substances. To investigate the effects of dietary supplementation with fermented heat-treated rice bran on the performance, apparent digestibility of nutrients, cecal microbiota and metabolites in laying hens, a total of 128 18-week-old Hy-Line brown layers were randomly assigned to four treatment groups: 2.5% HRB (basal diet contained 2.5% heat-treated rice bran), 5.0% HRB (5.0% heat-treated rice bran), 2.5% FHRB (2.5% fermented heat-treated rice bran), 5.0% FHRB (5.0% fermented heat-treated rice bran). Results showed that FHRB supplementation significantly increased the average daily feed intake (ADFI) during 25–28 weeks, and improved apparent digestibility of dry matter (DM), crude protein (CP), ether extract (EE) and crude fiber (CF) in laying hens. Moreover, feeding 5.0% of HRB and FHRB resulted higher egg production (EP) and average egg weight (AEW) during the feeding period, and decreased the feed conversion ratio (FCR) during 21 to 28 weeks. The alpha and beta diversity indices indicated that FHRB altered the cecal microbiota. In particular, dietary supplementation with FHRB significantly increased the relative abundances of Lachnospira and Clostridium. Compared with the 2.5% level of supplementation, supplementing 5.0% HRB and 5.0% FHRB increased the relative abundances of Firmicutes, Ruminococcus and Peptococcus, and lowered the relative abundance of Actinobacteria. Furthermore, dietary FHRB supplementation significantly increased the concentration of short-chain fatty acids in cecum and changed the overall metabolome. The results of correlation analysis showed a close interaction between cecal microbiota, metabolites and apparent digestibility of nutrients. Taken together, we revealed that FHRB supplementation can induce characteristic structural and metabolic changes in the cecal microbiome, which could potentially promote nutrient digestion and absorption, and improve the production performance of laying hens.